The Artistic Meaning of Isolo Tradition of Sentani Tribe, Papua in Indonesia's Sustainable Maritime Culture - Peradantha, Ida Bagus Gede Surya; Widyastutieningrum, Sri Rochana; Soewarlan, Santosa; Triguna, Ida Bagus Gde Yudha (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
The purpose of this study is to uncover the aesthetic meaning in the Sentani Tribe's Isolo tradition in Lake Sentani, Papua. The study focused on how the artistic aspects of Isolo represent essential creative meanings and what the important implications of artistic meanings in the Isolo tradition are for the development of the archipelago's sustainable maritime culture. This study employs a qualitative technique based on Roland Barthes' semiotic theory. Data was gathered through observation of Isolo performances during the 2023 Lake Sentani Festival, interviews, and literature searches. The following are the study's findings: First, creative components such as dance moves, singing, clothes, property, and body painting motifs demonstrate symbolic connotations of natural prosperity, patriotism, spirituality, and fraternity. Second, the key meanings in Isolo derive from the concept of Rokhabia, a sense of brotherhood of one womb that is deeply established in Sentani tradition. Third, the implications of the Isolo tradition might build Sentani tribe social relationships through the meaning of the elements in its artistic representation. This study contributes significantly to expanding the horizon of the Sentani Tribe's Isolo heritage in preserving Indonesia’s sustainable maritime culture.